Parametric Study of a Single Effect Lithium Bromide-Water Absorption Chiller Powered by a Renewable Heat Source - Tawalbeh, Muhammad (2020)
This work investigates the performance of a single-effect absorption chiller utilizing an aqueous lithium bromide solution as the working fluid and driven by hot fluid rejected from either a geothermal power plant or the outlet of a thermal solar collector. This relatively low enthalpy return fluid, which will otherwise be reinjected back into the earth, will be utilized as the thermal energy source of the chiller. Although such chillers are considered low-grade energy refrigeration cycles, the one proposed here has an advantage in terms of economy and efficiency. A parametric analysis is performed using Engineering Equation Solver software and is used to highlight the effect of the heat exchanger size on the coefficient of performance of the chiller. The analysis proved that the proposed device can operate with excellent cooling capacity, reaching 16 kW, and a relatively high coefficient of performance (~ 0.7) while being driven by the low-grade energy. The heat source temperature, solution heat exchanger effectiveness and the size of the absorber were shown to be key parameters for the design and operation of absorption chillers. Moreover, increasing the heat source mass flow rate has a significant impact on both cooling capacity and coefficient of performance at low values (< 10 kg/s) and unnoticeable impact at higher values (> 10 kg/s).